EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN FLASHCARD DALAM MENINGKATKAN PENGUASAAN KOSAKATA BAHASA INGGRIS SISWA SD NEGERI KALIBANTENG KIDUL 03 KOTA SEMARANG - Siti Amara Fadilla; Arum Dwi Kartika; Alfiana Eka Agustina; Ardaeta Nadia Rahmawati; Faisa Zahro; Dewi Asyikhah; Nurul Afifah; Lainatul Mudzkiyyah (Universitas Mahendradatta, 2025)
Flashcard is one of the tools used for teaching. Flashcard is widely used by teachers in schoolsto teach students English. The aim is to see the effectiveness of using flashcard media inimproving English vocabulary mastery at SD Negeri Kalibanteng Kidul 03, Semarang City.Using a quantitative experimental method with a non-random pre-test and post-test controlgroup design. The research sample consisted of 20 students of class 3B who were divided into2 groups selected using quota sampling techniques. The data collection method was throughstudent answers to questions. The data analysis technique used an independent sample t-test,the results of this study showed that p = 0.633 (p> 0.05), meaning that the results of thehypothesis in this study were rejected because there was no effect of using flashcard media inimproving English vocabulary mastery. The results of the Wilcoxon Signed-Rank test for thecontrol group showed t = 4.90 with p <0.01, indicating that the flashcard learning methodsucceeded in significantly improving students' vocabulary mastery. However, the experimentalgroup, although showing improvement, did not reach the same level of significance with t =3.53 and p < 0.05, meaning that the improvement was not strong enough to be consideredstatistically effective. That is, indicating that there is no significant difference, perhaps becausethere are some external factors that affect the learning process.